ANALISIS PENGARUH TERORISME, FLUKTUASI NILAI TUKAR, DAN STABILITAS POLITIK TERHADAP VOLATILITAS INDEKS SAHAM DI 3 NEGARA ASEAN + AS - Alviyandi Lim; Nuning Trihadmini (Media Ekonomi, 2021)
This study aims to analyze the effect of terrorism activity, exchange rate volatility, and political stability on stock index volatility, with a sample of four countries, namely: Indonesia, Thailand,  Philippines and the United States. This analysis is carried out by combining the GARCH-PANEL model, with an observation period from January 1, 2003 to December 31, 2017. The results of the study show that terrorism activities, exchange rate fluctuations, and political stability have a significant effect on capital market volatility. Among these variables, political stability has the greatest influence, followed by terrorist activity and lastly, exchange rate volatility. Terrorist activities have a negative impact on the stock index, because it causes an unfavorable investment climate so that the volatility of the stock index increases.